Pero García Cerezo or the Strength of the Rural Market in Late Medieval Extremadura (Edad Media. Revista de Historia, 2024)
This article aims to offer an integrative vision of commercial spaces, as an alternative to the logic of confrontation imposed by certain theoretical constructions on the rural economy, as well as the prominence of the rural market in the transition to Modernity, capable of emerging as a response to internal demand. In the context of the Castilian economy of the 15th century, the analysis of Puebla de Guadalupe (Cáceres) reveals the energizing role of the pecheros —free men subject to tribute— as economic agents. Although this study focuses on the figure of a butcher, it provides an overview of rural entrepreneurs, a local elite able to integrate local production into new economic practices.
Keywords: rural economy; local actors; diversification; entrepreneurial minority; initiative